2018
DOI: 10.1021/acs.analchem.8b02611
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Microbial Identification and Antibiotic Resistance Detection by Mass Spectrometric Analysis of Membrane Lipids

Abstract: Infectious diseases have a substantial global health impact. Clinicians need rapid and accurate diagnoses of infections to direct patient treatment and improve antibiotic stewardship. Current technologies employed in routine diagnostics are based on bacterial culture followed by morphological trait differentiation and biochemical testing, which can be time-consuming and labor-intensive. With advances in mass spectrometry (MS) for clinical diagnostics, the U.S. Food and Drug Administration has approved two micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 49 publications
0
51
0
1
Order By: Relevance
“…3a and c). Phospholipids are a major constituent of microbial cell membranes (35), and changes in environmental conditions can modulate cell membrane phospholipid composition of microbial communities (36)(37)(38). As such, the most abundant lipids on the chitin islands were signatures of specific microorganisms that grew on chitin under the different moisture regimes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a and c). Phospholipids are a major constituent of microbial cell membranes (35), and changes in environmental conditions can modulate cell membrane phospholipid composition of microbial communities (36)(37)(38). As such, the most abundant lipids on the chitin islands were signatures of specific microorganisms that grew on chitin under the different moisture regimes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recent work by our group introduces a novel extraction method that takes less than 1 h and bypasses the overnight lyophilization step without sacrificing spectral quality. This reduces the turnaround time to that of MALDI-TOF ID of microbial proteins, making this platform far more rapid than culture-based diagnostics for species identification and AST (37).…”
Section: Discussionmentioning
confidence: 99%
“…With another approach focusing on mass spectrometric analysis of membrane lipids, it was demonstrated that bacterial glycolipids possess species-specific characteristics allowing bacterial identification (Leung et al, 2017). Next, a lipidextraction protocol was described (Liang et al, 2019) that reduces the identification time to <1 h. This method has been tested to detect antibiotic-resistance and to identify microbes, without requiring culture, using a library of the clinically relevant ESKAPE pathogens and colistin-resistant pathogens expressing the mcr-1 gene in trans. Different biomarkers of resistance were found: mcr-1-containing P. aeruginosa strains showed a mass shift, 1,446-1,569 m/z, deriving by a PEtN ( m/z 123) addition to lipid A.…”
Section: Identification Of Biomarkers Associated With Drug-resistancementioning
confidence: 99%